Pathogenesis of COVID‐19 described through the lens of an undersulfated and degraded epithelial and endothelial glycocalyx. Issue 1 (4th December 2021) - du Preez, Heidi N.; Aldous, Colleen; Hayden, Melvin R.; Kruger, Hendrik G.; Lin, Johnson
Abstract: The glycocalyx surrounds every eukaryotic cell and is a complex mesh of proteins and carbohydrates. It consists of proteoglycans with glycosaminoglycan side chains, which are highly sulfated under normal physiological conditions. The degree of sulfation and the position of the sulfate groups mainly determine biological function. The intact highly sulfated glycocalyx of the epithelium may repel severe acute respiratory syndrome‐related coronavirus 2 (SARS‐CoV‐2) through electrostatic forces. However, if the glycocalyx is undersulfated and 3‐ O ‐sulfotransferase 3B (3OST‐3B) is overexpressed, as is the case during chronic inflammatory conditions, SARS‐CoV‐2 entry may be facilitated by the glycocalyx. The degree of sulfation and position of the sulfate groups will also affect functions such as immune modulation, the inflammatory response, vascular permeability and tone, coagulation, mediation of sheer stress, and protection against oxidative stress. The rate‐limiting factor to sulfation is the availability of inorganic sulfate. Various genetic and epigenetic factors will affect sulfur metabolism and inorganic sulfate availability, such as various dietary factors, and exposure to drugs, environmental toxins, and biotoxins, which will deplete inorganic sulfate. The role that undersulfation plays in the various comorbid conditions that predispose to coronavirus disease 2019 (COVID‐19), is also considered. The undersulfated glycocalyx may not only increase susceptibility to SARS‐CoV‐2 infection, but would also result in a hyperinflammatory response, vascular permeability, and shedding of the glycocalyx components, giving rise to a procoagulant and antifibrinolytic state and eventual multiple organ failure. These symptoms relate to a diagnosis of systemic septic shock seen in almost all COVID‐19 deaths. The focus of prevention and treatment protocols proposed is the preservation of epithelial and endothelial glycocalyx integrity.